Republic of Korea : Report on the Observance of Standards and Codes (ROSC) Data Module. (IMF Staff Country Reports; Country Report ;, 2003)
This report assesses Korea's data dissemination practices against the IMF's Special Data Dissemination Standard (SDDS) and is complemented by an in-depth assessment of the quality of the key macroeconomic datasets for the national accounts, prices, government finance, monetary, and balance-of-payments statistics. The assessment reveals that Korea meets the SDDS specifications for the coverage, periodicity, and timeliness of all data categories, and for the dissemination of advance release calendars. All agencies demonstrate professionalism, are transparent in their statistical practices and policies, and provide ethical guidelines to their staff.